Специфіка соціокультурної адаптації - Попович, О.В. (Культура народов Причерноморья, 2013)
З позицій принципу адаптації естетичний модус, а також творчість розглядаються як
необхідний конструктивний момент перетворювальної життєдіяльності людини.
Естетичні почуття, що виникають на основі переживань, можуть виникати тільки в результаті
гармонійного поєднання естетичних властивостей природи та активної соціально-адаптивної творчої
діяльності людини. Через засвоєння естетичного досвіду та його подальше використання в
культуротворчій діяльності відбувається соціокультурна адаптація людини. С позиций принципа адаптации эстетический модус, а также творчество
рассматриваются как необходимый конструктивный момент преобразовательной жизнедеятельности
человека.
Эстетические чувства, возникающие на основе переживаний, могут возникать только в результате
гармоничного сочетания эстетических свойств природы и активной социально-адаптивной творческой
деятельности человека. Через усвоение эстетического опыта и его дальнейшее использование в
культуротворческой деятельности происходит социокультурная адаптация человека. From the standpoint of the principle of adaptation aesthetic mode, and creativity are seen as a
necessary structural point of the human life transformation. One of the successful consequence of the human
adaptation to changes in the external environment, their established balance with the environment, or individual acts of optimal interaction with it is to achieve such an internal state, which characteristics are correlated with
those attributes contained in the concept of "harmony."
Regarding the system , harmony is a sign of coherence and co-ordination of actions, balance measurement of its
elements, which causes the appearance of aesthetic senses. In the case of the achieved harmony between a
human being and objective reality, there is a particular aesthetic pleasure when a person feels delight of the
usefulness of their being. The harmony in the concurrence of two aspects - internal and external - in the process
of human activity provides an optimal level of sociocultural adaptation. Achieving an appropriate level of
sociocultural adaptation shall be subjected to the conscious selection by a human the very way of behaving
through which the external activity can give feeling of satisfaction, such an important condition for adaptation.
Aesthetic sense, arising from experiences can occur only as a result of a harmonious combination of nature and
aesthetic properties of the active social and adaptive human creativity. Sociocultural adaptation goes through
the mastering the aesthetic experience and its subsequent use in a culture activity.
The socio-cultural adaptation is manifested as a mediate between phenomena of compensation and socialization.
The very aspect of the relationship, interdependence and interaction of the phenomena of adaptation,
compensation and socialization needs further philosophical analysis in these studies.